Melahirkan Paradigma Kebijakan Dividen Melalui Agency Cost - Carissa Fitri Nasywa; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Agency problems that arise between shareholders and management often become a primary driver in shaping corporate dividend distribution decisions. This study aims to examine the effect of agency cost, proxied by institutional ownership, insider ownership, free cash flow, and collateralizable asset, on dividend policy. The sample of this study consists of energy sector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The sampling technique used purposive sampling, resulting in 16 companies that met the research criteria. This study employs a quantitative approach using secondary data obtained from companies’ annual reports. The data analysis technique used is multiple linear regression analysis and dividend policy is measured using the dividend payout ratio. Research results show that institutional ownership and collateralizable asset have effect on dividend policy, meaning that the greater the institutional ownership, the more the company is encouraged to distribute dividends. Institutional oversight mitigates agency problems and encourages disciplined management. Pledged assets also influence dividend policy, indicating that asset structure affects profit distribution decisions. Meanwhile, insider ownership and free cash flow have no effect on dividend policy.